Factors Associated With Increased Mortality in Severe Abdominopelvic Injury. Issue 2 (February 2022) - Patel, Neerav; Harfouche, Melike; Stonko, David P.; Elansary, Noha; Scalea, Thomas M.; Morrison, Jonathan J.
ABSTRACT: Background: Associated injuries are thought to increase mortality in patients with severe abdominopelvic trauma. This study aimed to identify clinical factors contributing to increased mortality in patients with severe abdominopelvic trauma, with the hypothesis that a greater number of concomitant injuries would result in increased mortality. Methods: This was a retrospective review of the Trauma Quality Improvement Program (TQIP) database of patients ≥ 18 years with severe abdominopelvic trauma defined as having an abdominal Abbreviated Injury Score (AIS) ≥ 3 with pelvic fractures and/or iliac vessel injury (2015–2017). Primary outcome was in-hospital mortality based on concomitant body region injuries. Secondary outcomes included mortality at 6 h, 6 to 24 h, and after 24 h based on concomitant injuries, procedures performed, and transfusion requirements. Results: A total of 185, 257 patients were included in this study. Survivors had more severely injured body regions than non-survivors (4 vs. 3, P  < 0.001). Among those who died within 6 h, 28.5% of patients required a thoracic procedure and 43% required laparotomy compared to 6.3% and 22.1% among those who died after 24 h ( P  < 0.001). Head AIS ≥ 3 was the only body region that significantly contributed to overall mortality (OR 1.26, P  < 0.001) along with laparotomy (OR 3.02, P  < 0.001), neurosurgical procedures (2.82, P  < 0.001) and thoracic procedures (2.28, P  < 0.001). Non-survivors who died in < 6 h and 6–24 h had greater pRBC requirements than those who died after 24 h (15.5 and 19.5 vs. 8 units, P  < 0.001). Conclusion: Increased number of body regions injured does not contribute to greater mortality. Uncontrolled noncompressible torso hemorrhage rather than the burden of concomitant injuries is the major contributor to the high mortality associated with severe abdominopelvic injury.